The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4236/mrc.2020.91001
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Ag/TiO2 by Photoreduction Method and Its Degradation Activity of Methylene Blue under UV and Visible Light Irradiation

Abstract: A series of Ag/TiO 2 with various Ag contents were prepared by photoreduction method. Commercial TiO 2 from Evonik-Degussa was used as the catalyst. Ag was used as the cocatalyst. This facial synthesis method is cheap and easy. TiO 2 was suspended in water with various concentrations of silver nitrate. The solution was illuminated by UV light for 36 h. Ag would deposit on the surface of TiO 2. This method can deposit all Ag cation in the starting material on TiO 2 after 36 h irradiation by UV light. X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The presence of AgO crystals is due to the synthesized Ag/TiO 2 samples encountering air after the preparation process, which oxidizes Ag 0 to AgO. 15…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of AgO crystals is due to the synthesized Ag/TiO 2 samples encountering air after the preparation process, which oxidizes Ag 0 to AgO. 15…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the recombination rate was slowed, and Ti 3+ and O 2– production was accelerated. 15 It can be concluded that adding Ti 3+ and O 2– production causes an increase in the oxygen vacancies produced, making the surface more hydrophilic. This is because water can easily fill the space and produce adsorbed OH groups, which form a monolayer on the surface, as shown in Figure 9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…to tune the band structure of TiO 2 semiconductor by doping with Ag metal in order to boost the visible-light absorption without diminishing photocatalytic efficiency [ 26 , 28 , [35] , [36] , [37] , [38] ]. The excitation spectra of anatase Ag–TiO 2 NCs were achieved by detecting photons emitted from the atoms in the excited state at an emission wavelength of 285 nm in the TiO 2 emission-range while scanning the excitation for different wavelengths in the TiO 2 absorption-range.…”
Section: Resultsmentioning
confidence: 99%
“…The advantages of TiO 2 are high chemical stability, non-toxicity and low cost . Pd, Ag and Cu et al have been used as the cocatalysts of TiO 2 by facilitating electron transfer and therefore inhibiting electron-hole recombination, as well as by improving the photocatalytic response under the visible region [21,22,[26][27][28][29][30][31][32][33][34]. However, most of the studies on photocatalytic reaction were carried out at room temperature .…”
Section: Introductionmentioning
confidence: 99%